PREPRATION AND STORAGE OF BLENDED READY-TO-SERVE BEVERAGE FROM BAEL AND ALOE VERA - DHIRU KUMAR TIWARI,; BHAGWAN DEEN, (The Bioscan, 2014)
The RTS beverage prepared from blend consisting 75 % bael pulp and 25 % aloe vera gel was found the most acceptable than other blend combinations (0 and 100 %, 100 and 0 %, 50 and 50 % and 25 and 75 % bael pulp and aloe vera gel respectively). The RTS was organoleptically acceptable upto 3 months of storage at ambient temperature (24.4-38.5ºC). During the storage studies total soluble solids, acidity, reducing sugar, total sugars and browning increased whereas, vitamin C, non- reducing sugar content and organoleptic score decreased with storage period. The overall acceptability score (organoleptic score) of blended RTS was decreased from 8.17 at first day of storage to 7.50 at last day of storage. This study indicated that bael and aloe vera can be utilized for valuable RTS beverage making which can be beneficial for the consumers in terms of taste, colour, flavour and medicinal properties.